Lebanon : 2016 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Lebanon. (IMF Staff Country Reports; Country Report ;, 2017)
This 2016 Article IV Consultation highlights that Lebanon's economic growth remains subdued. Following a sharp drop in 2011, growth edged upward briefly to 2-3 percent, but has now slowed again. The IMF staff estimates that GDP increased by 1 percent in 2015, and a similar growth rate in 2016 is projected. Lebanon's traditional growth drivers-tourism, real estate, and construction-have received a significant blow and a strong rebound is unlikely based on current trends. In the absence of a turnaround in confidence, or a resolution of the Syrian conflict, growth is unlikely to return to potential (4 percent) soon.